Reversão de função de estímulos matemáticos com procedimentos de discriminação em escolares com ansiedade à matemática - Fioraneli, Rogério Crevelenti (2017)
The presence of aversive control during mathematics teaching can produce a response pattern called mathematics anxiety, which involves escape and avoidance every time an individual is requested to use mathematical knowledge; besides negative physiological reaction, and negative self-attributions. Typically individuals with math anxiety, besides its mathematics difficulties, forms conceptual classes in which mathematics stimuli are associated to unpleasant and punitive events. The literature about reversals of equivalent stimuli classes has pointed out promising directions, but none study has yet been conduct to document the reversals of negative meanings of math stimuli present on pre-experimental classes of math anxiety individuals. The present study aims to: (1) reverse pre-experimental classes formed by math stimuli; (2) establish a new class with positive social aspects and math stimuli; (3) ample the data about reversals of equivalence classes; (4) inaugurate studies about reversals of classes containing pre-experimental and aversive math stimuli in individuals with math anxiety. Three studies were conducted with primary school students who presented anxiety about mathematics in response to a specific scale. The procedure will consist of pre, training and post tests involving stimuli reinforcing social patterns, non-reinforcing social patterns, abstract forms, numeric visual stimuli and reinforcing social situations. According to the results, it can be inferred that the participants showed emergence of equivalent relations, but with inconsistent data on transfer of function between the members of the established classes.